The Holy Land in transit: Colonialism and the quest for Canaan. - Salaita, Steven. (My University, 2003)
Through a comparative analysis of colonialism in the New World and Holy Land with attention to how politics influence literary production, I examine the process by which settler societies transform theological narratives into national histories to justify their occupation of foreign land. In particular, I analyze the similarities between rhetoric employed by early colonialists in North America and that employed by Zionist immigrants in Palestine. In doing so, I examine histories, theories, and literary depictions of colonialism and inter-ethnic dialectics. Having established this comparative analysis, I then develop it further through the textual criticism in the second half of the dissertation, where I discuss Anishinaabe authors Gerald Vizenor and Winona LaDuke and Palestinian authors Liyana Badr and Emile Habiby.
Keywords: ÔΩ̜abibi, Imil Criticism and interpretation.; Arabic literature Palestine History and criticism.; Literature, Comparative.; Vizenor, Gerald Robert, 1934- Criticism and interpretation.; Literature, Middle Eastern.; American literature Indian authors History and criticism.; Literature, American.; LaDuke, Winona Criticism and interpretation.; Badr, Liyanah Criticism and interpretation.